Phosphorus removal in domestic wastewater treatment plant by calcined eggshell - Fritzen, Rafael Renato (2021)
Recovery of phosphorus (P) from wastewater is a topic of great interest. Besides being a non-renewable resource, P discharge in receiving waters can trigger algae blooms. The present study aimed to quantify the removal of P from two sites at a wastewater treatment plant using calcined eggshell (CES) as adsorbent. CES was prepared from raw shells calcined at 600 °C (CES600) and 800 °C (CES800). CES at 800 °C proved to be an efficient material for P removal. Efficiencies greater than 70% were achieved using CES800 concentrations of 0.1 g L 1 for synthetic sample, 0.3 g L 1 for preliminary treated wastewater and 20 g L 1 for supernatant from sludge anaerobic digester. The adsorption process was fast, occurring mostly in the first 30 min. Both Langmuir and Freundlich isotherms fitted the experimental data on adsorption. In kinetic experiments, a pseudo-second-order model fitted P adsorption from synthetic, preliminary effluent and digester supernatant. Thermogravimetric analysis showed a 54% eggshell mass loss at 800 °C. Calcination increased calcium and reduced carbon fractions in the eggshells, while increasing the surface area.